Reintegration of School Farms as a Panacea for Food Insecurity: Perspectives of Primary School Students in Edo State, Nigeria - Koledoye, Gbenga F. (Asian Journal of Science and Applied Technology, 2023)
This study investigated the attitudes of primary school students towards the establishment of school farms, utilizing a sample of 86 students from three public primary schools in Uhunmwode Local Government Area (LGA). Data were collected through questionnaires and interviews. The findings indicate that primary school children in Edo State generally support the idea of implementing school farms. Key factors contributing to this positive response include the availability of land and the potential to obtain additional land from local communities for agricultural purposes. Critical elements identified for the successful establishment of school farms encompassed the interest of both students and teachers, the presence of agricultural science instructors, and access to suitable farming land.